2021
DOI: 10.1111/epi.16989
|View full text |Cite
|
Sign up to set email alerts
|

Changes in epileptogenicity biomarkers after stereotactic thermocoagulation

Abstract: Objective Stereo‐electroencephalography (SEEG)‐guided radiofrequency thermocoagulation (RF‐TC) aims at modifying epileptogenic networks to reduce seizure frequency. High‐frequency oscillations (HFOs), spikes, and cross‐rate are quantifiable epileptogenic biomarkers. In this study, we sought to evaluate, using SEEG signals recorded before and after thermocoagulation, whether a variation in these markers is related to the therapeutic effect of this procedure and to the outcome of surgery. Methods Interictal segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…CT-scan/MRI data co-registration was performed, to check the anatomical location of each contact along the electrode’s trajectory, using the open-source software GARDEL ((Medina Villalon et al, 2018). For each patient, clinicians associated to each bipolar channel a ROI tagged as EZ, PZ or non-identified (NI), based on the Epileptogenicity Index method (Bartolomei et al, 2008), full details on the data acquisition and EZ designation by clinicians are provided in (Bartolomei et al, 2008; Contento et al, 2021). Time intervals of the order of one to 20 seconds around the clinicians specified seizure onset time were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…CT-scan/MRI data co-registration was performed, to check the anatomical location of each contact along the electrode’s trajectory, using the open-source software GARDEL ((Medina Villalon et al, 2018). For each patient, clinicians associated to each bipolar channel a ROI tagged as EZ, PZ or non-identified (NI), based on the Epileptogenicity Index method (Bartolomei et al, 2008), full details on the data acquisition and EZ designation by clinicians are provided in (Bartolomei et al, 2008; Contento et al, 2021). Time intervals of the order of one to 20 seconds around the clinicians specified seizure onset time were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Channels were labeled as either thermocoagulated (TC) or not (non-TC) and as either involved (INV) or noninvolved (non-INV) in the epileptogenic network. 7 Involved channels included channels in the epileptogenic zone and in the propagation zone (as defined by clinicians during the SEEG clinical investigation). The remaining channels were labeled as noninvolved.…”
Section: Influences Of Other Factors On Fc or Psd Changes)mentioning
confidence: 99%
“…Recent studies have shown that RF-TC induces changes in the rates of epileptic spikes and high-frequency oscillations that are related to the clinical outcome of the procedure. 6,7 It is now established that epilepsy is a network disease, affecting spread brain areas rather than a focal region. [8][9][10] Russo and colleagues 11 recently demonstrated that thermocoagulation-induced focal lesions lead to an increase of slow wave activity (delta band range, 0.5 Hz to 4 Hz) both in the perilesional area and in the regions connected to that area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations